Karyological notes on seven Trifolium L. taxa from Turkey - Kıran, Y.; Şahin, A.; Türkoğlu, İ.; Emre, İ.; Kurşat, M. (Fırat University, 2015)
Three basic chromosome counts (x:5, 7 and 8) were determined in this study. It was found that T. resupinatum L. var. resupinatum, T. stellatum L. var. stellatum and T. purpureum Lois. var. purpureum have 2n: 16; T. arvense var. arvense, T. hausknechtii Boiss. var. hausknechtii and T. pauciflorum d’Urv. have 2n.14; T. hirtum has 2n:10 chromosome numbers according to the present results. All chromosomes have median point (M), median region (m) centromeres and satellites were not observed in the studied Trifolium taxa. The chromosome number and morphology of T. haussknechtii Boiss. var. haussknechtii and T. pauciflorum d’Urv. are reported for the first time.

Bu çalışmada üç temel kromozom sayısı belirlendi (x:5,7 ve 8). Mevcut bu çalışmaya göre T. resupinatum L. var. resupinatum, T. stellatum L. var. stellatum ve T. purpureum Lois. var. purpureum 2n: 16; T. arvense var. arvense, T. hausknechtii Boiss. var. hausknechtii ve T. pauciflorum d’Urv. 2n.14; ve T. hirtum 2n:10 kromozom sayısına sahiptir. Çalışılan Trifolium türlerinde bütün kromozomlar, median noktalı (M), median (m) olarak bulundu ve satellit gözlenmedi. T. haussknechtii Boiss. var. haussknechtii ve T. pauciflorum d’Urv.’nin kromozom sayıları ve morfolojileri ilk kez rapor edilmiştir.
Türkiyedeki Yedi Türkiyedeki Yedi Trifolium L. Üzerine Karyolojik Notlar